Calcitonin Gene-Related Peptide (CGRP) in Cerebrovascular Disease - Lars Edvinsson (The Scientific World Journal)
Cerebral blood vessels are innervated by sensory nerves that store several neurotransmitters among which calcitonin gene-related peptide (CGRP) is the most abundant. In primary headaches, there is a clear association between the head pain and the release of CGRP. In cluster headache there is an additional release of vasoactive intestinal peptide (VIP).